2012
DOI: 10.1107/s0021889812015038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polycrystallinity in hen egg-white lysozyme using a pnCCD

Abstract: A crystal of hen egg‐white lysozyme was analyzed by means of energy‐dispersive X‐ray Laue diffraction with white synchrotron radiation at 2.7 Å resolution using a pnCCD detector. From Laue spots measured in a single exposure of the arbitrarily oriented crystal, the lattice constants of the tetragonal unit cell could be extracted with an accuracy of about 2.5%. Scanning across the sample surface, Laue images with split reflections were recorded at various positions. The corresponding diffraction patterns were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…However, with emerging energy resolving detectors, access to the full strain tensor can be realized in the future (see for example Ref. [40]). This energy resolution will also ensure that higher levels of imposed load can be examined since crystallographic indexation will be more straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…However, with emerging energy resolving detectors, access to the full strain tensor can be realized in the future (see for example Ref. [40]). This energy resolution will also ensure that higher levels of imposed load can be examined since crystallographic indexation will be more straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Auch tiefenaufgelçste Messungen sind mit 3DXRD-Ansätzen wie Differential-Aperture X-ray Microscopy [1b] mçglich, jedoch muss hierbei zeitintensiv eine Blende durch den Strahl gerastert werden. Trotz seiner sehr geringen Grçße wurde er erfolgreich zur Bestimmung von Zwillingsbildung in Lysozymkristallen [10] ,d er Gitterverzerrung in Kupfer-Einkristallen [11] oder der Indizierung von GaAs-Einkristallen mit harten Rçntgenstrahlen verwendet, [12] wobei die Experimente nur einen kleinen Winkelausschnitt des reziproken Raums erforderten. Einige Ansätze wurden durch die Verwendung von energieauflçsenden Punktdetektoren bereits realisiert.…”
Section: Rçntgenbeugung (Xrd) Ist Eine Wertvolle Methode Zurunclassified
“…[8] Ein großer Fortschritt in dieser Hinsicht war die Entwicklung eines energieauflçsenden Flächendetektors (Rçntgenfarbkamera, pnCCD), [8,9] der im Prinzip energieauflçsende Laue-Beugung (EDLD) ermçglicht. Trotz seiner sehr geringen Grçße wurde er erfolgreich zur Bestimmung von Zwillingsbildung in Lysozymkristallen [10] ,d er Gitterverzerrung in Kupfer-Einkristallen [11] oder der Indizierung von GaAs-Einkristallen mit harten Rçntgenstrahlen verwendet, [12] wobei die Experimente nur einen kleinen Winkelausschnitt des reziproken Raums erforderten.…”
Section: Rçntgenbeugung (Xrd) Ist Eine Wertvolle Methode Zurunclassified
“…In this application, exploiting also the time resolution of the pnCCD, fourdimensional data sets were generated, containing the desired structural information about the material. Moreover, pnCCD systems have been applied for energy-dispersive Laue diffraction techniques in inorganic and macromolecular crystallography (Send et al, 2009(Send et al, , 2012. It was shown that both for single-and for polycrystalline materials unit-cell determination can be achieved with high accuracy by energy resolution of the recorded Laue pattern and conversion of the threedimensional spot coordinates into reciprocal space.…”
Section: Introductionmentioning
confidence: 99%